Pengaruh Beberapa Ekstrak Daun sebagai Pestisida Nabati terhadap Mortalitas Ulat Grayak (Spodoptera litura F.) dan Intensitas Kerusakan Daun Tanaman Pakcoy (Brassica rapa L.) - Sugiarto; Adelia Regina; Tatang Surjana (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2022)
Pakcoy (Brassica rapa L.) is one of the popular vegetables in Indonesia. One of the main pests of pakcoy is armyworm (S. litura) which has the potential to damage plants. The study aimed to obtain the most effective treatment of several leaf extracts as a natural pesticides to the mortality of armyworm (S. litura) and the intensity of the leafe damage of pakcoy (Brassica rapa L.). The research was conducted at the Laboratory and at Net House SMKN 1 Cikampek. The method used is an experimental method with the design of experiments used is a single factor Completely Random Design (CRD) and a single factor Random ized Block Design (RBD)consisting of 8 treatments in 4 repeats: A (Without Treatment), B (Carbosulfan insecticide 1 ml/l), C (Extract of Noni Leaf 300 g/l), D (Extract of Noni Leaf 400 g/l), E (Extracts of Soursop Leaf 45 g/l), F (Extracts of Soursop Leaf 60 g/l), G (Extracts of Papaya Leaf 300 g/l), and H (Extract of Papaya Leaf 400 g/l). The results showed that the administration of some leaf extracts as natural pesticides was influential to the mortality of armyworm (Spodoptera litura F.) and the intensity of the leaf damage of pakcoy (Brassica rapa L.). The natural pesticide of the Papaya Leaf Extract (400 g/l) gives the highest mortality 100.00%, and lowest leaf damage intensity 56.21%. Keyword : Extract, natural pesticides, armyworm, mortality and intensity of leafe damage, pakcoy.